Homoseksualitas dan Gereja: Menelusuri Pandangan, Respon dan Penanganannya - Elsyanti Gultom; Rencan Carisma Marbun (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
The purpose of this writing is to help readers and the Church of God better understand the response and role toward the existence of homosexuality, and to serve as a reference for the Church in addressing cases of homosexuality. The goal is to produce an effective perspective and approach that the Church and society should take in serving and healing individuals suffering from homosexuality. In this study, the Biblical perspective on homosexuality is analyzed by referencing key texts such as Leviticus 18:22 and Romans 1:26-27, which are often used as the basis for conservative churches to oppose homosexuality. This research also examines the Church's response in the form of guiding individuals toward repentance, commitment to celibacy, pastoral counseling, as well as attention to the psychological aspects of homosexual individuals. Using a qualitative approach, this study highlights significant differences in the Church's response to homosexuality, where conservative churches emphasize repentance and the avoidance of homosexual relationships, while progressive churches are more accepting and supportive of inclusivity. This research is expected to provide insight into the Church's role in supporting homosexual individuals and building a more inclusive understanding in line with the teachings of Christ's love.